Multimodal Pain Management and Challenges in Patients Undergoing Simultaneous Pancreas and Kidney Transplantation - Najbar, Joanna Monika; Chmura, Katarzyna; Zimnoch, Barbara Zimnocj; Rendaszka, Katarzyna; Kowalska, Katarzyna; Pyziołek, Marta; Bonarska, Marta; Kwaśniewska, Paulina; Stróżna, Małgorzata (Quality in Sport, 2025)
Background. Diabetic foot syndrome is a severe complication of diabetes mellitus, often complicated by infection, impaired wound healing, and chronic pain. Management is particularly challenging in patients with a history of simultaneous pancreas–kidney transplantation (SPK) and reduced renal function. Aim. To present a complex case of diabetic foot syndrome in a patient after SPK transplantation, highlighting the challenges of pain management and wound care in the context of opioid history and impaired kidney function. Case Presentation. A 65-year-old patient was admitted to the diabetic ward due to worsening pain associated with left diabetic foot syndrome. Physical examination revealed swelling, redness, and purulent discharge. The wound was cleaned, limb offloading was applied, and VAC/NPWT (vacuum-assisted closure/negative pressure wound therapy) was initiated, but the patient continued to experience pain, tension, and discomfort around the wound. Laboratory tests demonstrated decreased estimated glomerular filtration rate (eGFR), and increased levels of uric acid, keratin, and leukocytes. The patient had undergone SPK transplantation 1.5 years prior without complications. History of opioid abuse and limited kidney function posed significant restrictions on analgesic therapy. Conclusions. Diabetic foot syndrome in post-SPK patients presents a multifactorial clinical challenge, requiring careful management of infection, renal impairment, and pain. Individualized, interdisciplinary approaches are essential to optimize wound healing while minimizing opioid use and preventing further complications.